Builders at opposite poles, or pioneers of different quests? contrasting heidegger and sellars - Sanlı, Alptekin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The present thesis concerns the status of the conceptual in our experience of the world. The trajectory of my argument runs as follows: (1) Responding to a recent debate between professors Hubert L. Dreyfus and John McDowell, I argue, against Dreyfus, that the exercise of our conceptual capacities, far from being a detached transformation of our basic animal coping skills, constitutes an inalienable element of our openness to the world. This stage of the thesis is chiefly exegetical: I try to show that Dreyfus’s appeal to Heideggerian phenomenology as a laying out of the foundation upon which detached rationality grows is misplaced, in that Heidegger’s work does not seem to bear out such a claim. Neither is it possible to discern, in the work of Sellars, from which latter-day “conceptualists” such as McDowell take their cue, a useless pretension as to reducing all our perceptual skills to our inferential capacities. The gist of this first stage of my argument is that the very construal of these two influential thinkers as “building the edifice of human experience” from opposite ends is highly misleading. Such a construal diverts us from considering how each seek to illuminate our existence by different modes of questioning. (2) Next I try to show briefly that beyond the failure of the Dreyfusian exegeses of Heidegger and Sellars, it is difficult even to make sense of the very idea that human experience is arranged in levels. (3) What truly is at issue in the whole debate, I then claim, is not at all the status of rationality as a “transformation” or not, but rather the possibility of our responsibility to truth, as a defining factor of human comportment.